Study on the thermal decomposition rate of ammonium carbamate for a diesel NOx reducing agent-generating system. (1st May 2020) - Kim, Youngmin; Raza, Hassan; Lee, Sangho; Kim, Hongsuk
Highlights: A simple modeling of a reactor generating NOx reducing agent using ammonium carbamate. Sufficient amount of NH3 can be supplied to reduce NOx emitted from a diesel engine. Temperature affects on decomposition rate, reactor pressure and final remain AC mass. Reactor volume affects on pressure fluctuation, heating energy and refilling interval. Abstract: Ammonium carbamate (AC) is a substance that exists in solid state at room temperature and decomposes into ammonia and carbon dioxide upon heating. In this study, AC was thermally decomposed to produce ammonia gas, which is used as a reducing agent for reduction of NOx emitted from a diesel engine. Currently, most diesel engines utilize a UWS (urea-water solution) as a reducing agent. However, the need for significant heat energy for evaporation and thermal decomposition is one of the reasons driving low NOx reduction efficiency at low exhaust gas temperature conditions. On the other hand, the alternative method of supplying gaseous ammonia by thermal decomposition of solid AC has an advantage of relatively high NOx reduction efficiency at low exhaust gas temperature conditions. Recently, there have been studies on material properties of AC and system feasibility in order to use the AC as a diesel NOx reducing agent. In this study, a simple system for generating diesel NOx reducing agent upon thermal decomposition of AC was mathematically modeled. In addition, the thermal decomposition rate of the AC was expressed via an Arrhenius equation through TGA (thermo-gravimetric analysis) experiments, and the activation energy and pre-exponential factor of the Arrhenius equation were determined. Using the mathematical model and the Arrhenius equation of the thermal decomposition of AC, the effect of various parameters required for designing a reactor and system operation were investigated for a heavy-duty diesel engine with a displacement of 3.9 L.